Qudratu al Ṭullābi alā Nuṭqi Mufradāti al Lughati al ‘Arabiyyati bi al Madrasati al ‘Āliyati al Ḥukūmiyyati Jāmbi - Prihartini, Yogia; Wahyudi, Hakmi (Al-Uslub: Journal of Arabic Linguistic and Literature, 2020)
The purpose of this study was to determine the ability of students to express vocabulary to understand language, both through hearing and writing, and to be able to express their thoughts and feelings, both orally and in writing, as well as to determine student achievement in learning Arabic in Islamic Senior High Schools MAN of Jambi. This research methodology is characterized by qualitative descriptive and data collection methods are observation methods, interview methods, and documents. Data analysis includes field analysis, classification analysis, and combined analysis. The results of this study include: First, student motivation to learn Arabic at Islamic Senior High Schools MAN of Jambi is still very low. Second, the researcher found that most of the students had little interest in the lessons the Arabic teacher gave in front of the class. This is proof that students are not serious about taking lessons, some leave class and some are left behind when the teacher explains the material in front of the class, when the teacher asks the material presented, they do not understand the Arabic vocabulary material. If instructing students to read, most of them cannot read because of the students' weak pronunciation and understanding of Arabic vocabulary. Third, the factors that influence interest in learning Arabic include two factors, namely internal and external factors. As for the teacher's efforts to increase student motivation and ability in understanding Arabic vocabulary in Islamic Senior High Schools MAN Jambi by creating direct learning using mobile phones, learning materials are attached to the sophistication of communication tools and social media.